2020
DOI: 10.1111/arcm.12569
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature performance of two‐layered ceramics and the implications for Roman crucibles

Abstract: Roman metalworking crucibles are frequently characterized by an extra outer layer of clay, applied to a pre‐formed vessel. Three‐point bending and standardized dead‐weight loading tests were conducted to determine the advantages offered by the extra outer layer. Deformation and fracture behaviour, at temperatures up to 1100°C, of two‐layer, monolithic and tempered‐monolithic briquettes were compared. Measurements indicated that the two‐layer briquettes were more resistant to fracture at high temperatures: > 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Higher alumina contents in group B crucibles, similar to high alumina crucibles types 2 and 3 from Hedeby (Merkel 2016, p. 213), would enhance their heat resistance properties. Nevertheless, given that the Ribe crucibles are not highly refractory, additional layering to reduce the effects of brittleness (Rehren 2003;Bayley and Rehren 2007;Gardner et al 2020), might not have been needed, as exterior layering was found in just one crucible (base fragment ASR9 ×147.17, S7, no. 3).…”
Section: Metallurgical Ceramicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher alumina contents in group B crucibles, similar to high alumina crucibles types 2 and 3 from Hedeby (Merkel 2016, p. 213), would enhance their heat resistance properties. Nevertheless, given that the Ribe crucibles are not highly refractory, additional layering to reduce the effects of brittleness (Rehren 2003;Bayley and Rehren 2007;Gardner et al 2020), might not have been needed, as exterior layering was found in just one crucible (base fragment ASR9 ×147.17, S7, no. 3).…”
Section: Metallurgical Ceramicsmentioning
confidence: 99%
“…3). The increase in group B crucibles from the early to the later period suggests that more refractory fabrics were used after 790 CE, possibly based on the craftspeople's practical experience (Braun 1983;Freestone and Tite 1986;Gardner et al 2020). Alumina-rich crucibles were imported to Hedeby and Kaupang in the 9th c. (Pedersen 2010(Pedersen , p. 191, 2016Merkel 2016, p. 211) and later (eleventh c. CE) in Viborg, Denmark (Jouttijärvi and Andersen 2005, p. 356).…”
Section: Metallurgical Ceramicsmentioning
confidence: 99%
See 2 more Smart Citations